2015
DOI: 10.3892/mmr.2015.3645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesenchymal stem cells on interleukin-1β-treated chondrocytes and cartilage in a rat osteoarthritic model

Abstract: In the present study, the effects and mechanisms of mesenchymal stem cells (MSCs) on interleukin (IL)-1β-stimulated rat chondrocytes, as well as cartilage from a rat model of osteoarthritis (OA) induced by anterior cruciate ligament transection and medial meniscectomy were investigated. Confluent rat chondrocytes were treated with IL-1β (10 ng/ml), then cultured indirectly with or without MSCs at a ratio of 2:1. Total RNA and protein were collected at various time-points, and western blot and reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…More recently, Yang et al have demonstrated that treadmill exercise lowers MMP-13 expression in articular cartilage of rats with OA (27). In another study, MSC therapy significantly decreased expression of MMP-13 in rats with knee OA (28). Our findings indicate that exercise training, MSC and ozone therapies are helpful for OA improvement.…”
Section: Mmp13supporting
confidence: 61%
“…More recently, Yang et al have demonstrated that treadmill exercise lowers MMP-13 expression in articular cartilage of rats with OA (27). In another study, MSC therapy significantly decreased expression of MMP-13 in rats with knee OA (28). Our findings indicate that exercise training, MSC and ozone therapies are helpful for OA improvement.…”
Section: Mmp13supporting
confidence: 61%
“…Conditioned medium from nontransduced MSC had no protective effect and, instead, the contrary effect was observed, because chondrocytes treated with conditioned medium from stimulated and nonstimulated, nontransduced MSC revealed up‐regulation of IL‐6, IL‐8 and MMP1, as well as down‐regulation of COL2A1 genes. These observations were fairly unexpected because it is known that MSCs secrete factors inhibiting inflammatory processes and a protective effect of MSC co‐cultivated with IL‐1β‐treated chondrocytes in a rat osteoarthritic model was reported recently . We are aware that these expression changes are influenced by several parameters that are closely related to the experimental set‐up (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Chondrocytes were stimulated with 10 ng/ml of interleukin-1β (Gibco, United States) as previously described [15]. To assess the effect of CM on chondrocyte viability, cells were seeded at a density of 1 × 10 4 cells/cm 2 in 96 well plates (n = 4) and cultured for 48 h. At the end of 48 h, the medium was aspirated and the cells were incubated with DMEM/F-12 supplemented with 0.5% FBS for 12 h to allow the cells to synchronise.…”
Section: Chondrocyte Stimulation and Treatmentmentioning
confidence: 99%